KRITIK DAN EDISI TEKS NASKAH UNDANG-UNDANG NAGARI SALIMPAT KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Siska Afriani; Nurizzati Nurizzati; Zulfadhli Zulfadhli (Jurnal Bahasa dan Sastra, 2013)
This research amied to present, (1) a describtion of law script of Salimpat- Gumanti Valley subdistrict, Solok Regency; (2) the forms of writing errors and deviation of letter in law script of Salimpat- Gumanti Valley subdistrict, Solok Regency; and (3) the form of text edition law script of Salimpat- Gumanti Valley subdistrict, Solok Regency. Therefore, it could be read. This research used qualitative research that was focused on philology area, and the object of the study was law of Salimpat- Gumanti Valley subdistrict, Solok Regency. This research used standart edition method to do text edition. This research found letter errorrs, namely lacunae, substitution, haphlographie, and dittograhpy.  Besdies, deviation of letter, the form of writing errors were also found. The errors and deviation that were found repaired then. The law script of Salimpat- Gumanti Valley subdistrict, Solok Regency was translated into Indonesian and made in a new edition. Kata kunci : filologi, naskah, teks, kritik, edisi